Differential Effects of Prior Influenza Exposures on H3N2 Cross-reactivity of Human Postvaccination Sera - Xie, Hang (Clin Infect Dis, 2017)
BACKGROUND. Effectiveness of seasonal influenza vaccines mainly depends upon how well vaccine strains represent circulating viruses; mismatched strains can lead to reduced protection. Humans have complex influenza exposure histories that increase with age, which may lead to different postvaccination responses to emerging influenza variants. Recent observational studies also suggest that prior vaccination may influence the performance of current seasonal vaccines. METHODS. To elucidate the effects of age and influenza preexposures on cross-reactivity of vaccination-induced human antibodies, we generated antigenic maps based on postvaccination hemagglutination inhibition titers against representative H3 variants circulating during the 2015–2016, 2014–2015, and 2012–2013 influenza seasons. RESULTS. Antigenic maps determined using sera from subjects 18–64 and ≥65 years of age correlated well with each other but poorly with those determined using sera from children. Antigenic maps derived from human postvaccination sera with H1 influenza preexposure also correlated poorly with those derived from sera with neither H1 nor type B influenza preexposure, and the correlation lessened considerably over time. In contrast, antigenic maps derived from human postvaccination sera with only type B influenza preexposure consistently showed good correlation with those derived from sera with neither H1 nor type B influenza preexposure. CONCLUSIONS. Our results suggest an age-specific difference in human postvaccination responses. Our findings also suggest that prior exposure to H1 or type B influenza may differentially affect cross-reactivity of vaccination-induced H3-specific hemagglutination inhibition antibody responses, and consequently might affect vaccine effectiveness. Our study highlights the need to study the impact of prior exposure on influenza vaccine performance.